Prevalence and predictors of 25-OH vitamin D deficiency in peritoneal dialysis patients: A single center study - VELİOĞLU, ARZU; TUĞCU, MURAT; AŞICIOĞLU, EBRU; BARUTÇU ATAŞ, DİLEK; ARIKAN, İZZET HAKKI (My University, 2021)
Vitamin D has a critical role in bone-mineral disorders in chronic kidney disease (CKD) and its deficiency is further associated with increased cardiovascular morbidity and mortality among CKD patients. We aimed to evaluate prevalence of vitamin D deficiency and investigate the laboratory and clinical parameters associated with 25- OH vitamin D deficiency in peritoneal dialysis (PD) patients. Sixty-four (33M/31F) peritoneal dialysis patients were enrolled in this retrospective single center study. Clinical and laboratory data were obtained from patient charts. Prevalence of 25-OH vitamin D deficiency and its associations were analyzed. The patients’ mean age was 49.7±13.3 years and the mean duration of PD was 61.0±55.0 months. The mean 25-OH vitamin D level was 8.9±2.4 ng/ml and none of the patients were on 25-OH vitamin D therapy. All of the patients had lower than normal 25-OH vitamin D levels according to KDOQI guidelines. Levels of 25-OH vitamin D were deficient and insufficient in 84.4% (57.8% mild; 26.6% severe) and 15.6% of the patients, respectively. There was no association between 25-OH vitamin D levels and sex, age, BMI, duration of PD and cause of ESRD. There was a negative correlation between 25-OH vitamin D levels and uric acid and parathyroid hormone. Uric acid was an independent predictor of 25-OH vitamin D deficiency in the logistic regression analysis [OR (95%CI): 0.139 (0.029-0.667), p: 0.014]. We conclude that 25-OH vitamin D deficiency is very common in PD patients. Serum uric acid is an independent predictor of 25-OH vitamin D deficiency which should further be investigated in larger studies.
Keywords: 25-hydroxyvitamin D; parathyroid hormone; peritoneal dialysis; uric acid; vitamin D deficiency